O político na argumentação de um processo de injúria - Garcia, Marília Achete Junqueira (2008)
This research, intitled Designation and Argumentation in an Injury Process, is directed to an analysis of the argumentative movements in a process characterized as injury in which the designations trim diferent discursive memories of each enunciative occurency and in which the subjects division in the enunciation mark the division of each enunciative scene of the process, supporting by the argumentative operators to direct the argumentation meanings, since these meanings constitute the meanings of the text, as they trim certain interdiscursive regions. Thus, this research has as theoric aparate the Guimarães studies, and, then, institutes itself in the theoric-metodologic perspective of the Semântica Histórica da Enunciação and the Semântica Argumentativa. The process was estabilished after the denounce of a black police woman, who works at the Câmara Municipal de São Carlos, after hearing from her superior the department chef enunciations containing ofensive designations to her color and to her job. Aiming to analyse how the argumentation is built in the process and, consequently, how its meanings are constituted, considering that the argumentation is a process of the político, in a first moment is verified in which way the signos constitutive of the ofensive statements are valued by the interlocution subjects from the investigation of the social-historical values that get through the designations, supporting on, for this, in the Bakhtin and Guimarães theories. After being verified that the designations meanings are being constituted as injurious, I considered that it occurs the dissenso , defined by Rancière as the division of the sensible world that become the argumentation possible, and, because there is the dissenso, this space division in which occurs the enunciations, I get the conception that every process space of enunciation is político, is divided. Thus, is developed, at this moment of the research, the definition of polític, built by in his text Semântica do Acontecimento, since the político will get through all the enunciative relations of the legal text (the process, the law), and develop the concepts of temporalidade and acontecimento. But, because I consider that the dissenso estabilish the division, beggining the litígio, that I analise, firstly, in this chapter, the concepts of política and polícia drawned by Rancière. After being verified that the enunciation space of the process is political and ruled by a normativity, in which the subjects are ruled by its rights to enunciate and to the ways to enunciate, this means, conidering the reffered coertions of the ennciative space of the process, are drawned in the following chapter the manner of enunciability of the Manual Law Manual and in which way the discursive memory interacts to the construction of legal statements into the interdiscursive way, being supported by authours as Pêcheux, Orlandi et al. In the last chapter, at first are followed Ducrot and Anscombre steps, concerning to the argumentation for it, than, being developed and applyied the theories about enunciation and argumentation elaborated by Guimarães, having as the main focus the role of the argumentative operators in the construction of the argmentation meanings in the process